1985
DOI: 10.1104/pp.79.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 Enrichment and Carbohydrate Content on the Dark Respiration of Soybeans

Abstract: During the period of most active leaf expansion, the foliar dark respiration rate of soybeans (Glycine max cv Williams), grown for 2 weeks in 1000 microliters CO2 per liter air, was 1.45 milligrams CO2 evolved per hour leaf density thickness, and this was twice the rate displayed by leaves of control plants (350 microliters CO2 per liter air). There was a higher foliar nonstructural carbohydrate level (eg. sucrose and starch) in the CO2 enriched compared with CO2 normal plants. For leaves. These increases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 22 publications
4
46
2
Order By: Relevance
“…1) in plants grown at either ambient or elevated CO 2 were correlated with changes in mitochondrial number (Table IV) and maximum activity of cytochrome c oxidase (Table VI). Azcon-Bieto et al (1994), Hrubeck et al (1985), and Tissue et al (2002) also reported a correlation between the maximum activity of cytochrome c oxidase activity and respiration rates in trees, crops, sedges, and C3 and C4 grasses. These results suggest that the capacity of respiration is tightly regulated in plants (as suggested elsewhere; Gonzalez-Meler and Siedow, 1999; Atkin and Tjoelker, 2003) to maintain certain homeostasis between the capacity of respiration (mitochondrial counts, cytochrome c oxidase activity) and tissue-specific respiration rates, ) or elevated CO 2 (E, 600 mg mL 21 ) for 4 months.…”
Section: Co 2 During Growthmentioning
confidence: 99%
“…1) in plants grown at either ambient or elevated CO 2 were correlated with changes in mitochondrial number (Table IV) and maximum activity of cytochrome c oxidase (Table VI). Azcon-Bieto et al (1994), Hrubeck et al (1985), and Tissue et al (2002) also reported a correlation between the maximum activity of cytochrome c oxidase activity and respiration rates in trees, crops, sedges, and C3 and C4 grasses. These results suggest that the capacity of respiration is tightly regulated in plants (as suggested elsewhere; Gonzalez-Meler and Siedow, 1999; Atkin and Tjoelker, 2003) to maintain certain homeostasis between the capacity of respiration (mitochondrial counts, cytochrome c oxidase activity) and tissue-specific respiration rates, ) or elevated CO 2 (E, 600 mg mL 21 ) for 4 months.…”
Section: Co 2 During Growthmentioning
confidence: 99%
“…In the present study we (2,4,5,11,13). To determine the effect of high soluble carbohydrates on initial dark F2,6-P2 levels, three approaches were used for altering the soluble carbohydrate content of the leaf.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study this is what was observed. First, treatments that increase carbohydrate levels in photosynthetically active leaves consistently increase initial dark respiration rates (2,4,5,11,13). Initial dark F2,6-P2 and sucrose levels are considerably higher after longer photosynthetic periods, low temperature treatment, and when loss of carbohydrate is restricted by leaf excision (Table I; Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations